2020
DOI: 10.1088/2515-7620/ab7ee9
|View full text |Cite
|
Sign up to set email alerts
|

Monthly storminess over the Po River Basin during the past millennium (800–2018 CE)

Abstract: Reconstructing the occurrence of diluvial storms over centennial to millennial time-scales allows for placing the emergence of modern damaging hydrological events in a longer perspective to facilitate a better understanding of their rate of return in the absence of significant anthropogenic climatic forcing. These extremes have implications for the risk of flooding in sub-regional river basins during both colder and warmer climate states. Here, we present the first homogeneous millennium-long (800-2018 CE) tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…We use these factors (amounts of precipitation and weather anomalies) to develop a parsimonious model for reconstructing annual rainfall erosivity over the period 1500-2019 CE, allowing us to capture a wide range of climate variability, and identifying landscape-stress changes. The results of this study complement, for the past five centuries (1500-2019 CE), the twelve century-long (800-2018 CE) reconstructions of extreme hydro-meteorological events across Italy 56 and in the Po River Basin 70 .…”
Section: Introductionsupporting
confidence: 67%
“…We use these factors (amounts of precipitation and weather anomalies) to develop a parsimonious model for reconstructing annual rainfall erosivity over the period 1500-2019 CE, allowing us to capture a wide range of climate variability, and identifying landscape-stress changes. The results of this study complement, for the past five centuries (1500-2019 CE), the twelve century-long (800-2018 CE) reconstructions of extreme hydro-meteorological events across Italy 56 and in the Po River Basin 70 .…”
Section: Introductionsupporting
confidence: 67%
“…• Annual severity storm index sum (ASSIS): A categorical variable, the annual severity storm index sum (ASSIS), was derived from Diodato et al (2020c) to overcome the lack of historical information about rain intensity. ASSIS was developed based on several written sources, by transforming documentary information into a record set to 0 (normal event), 1 (stormy event), 2 (very stormy event), 3 (great stormy event) or 4 (extraordinary stormy event).…”
Section: Datamentioning
confidence: 99%
“…The original ASSIS time series of yearly values (Diodato et al 2020c) was smoothed by applying the low-pass Gaussian filtering technique described by Gjelten et al (2016). Weighting coefficients (w ij ) were applied to derive the Gaussian function, ASSIS(GF), for each year j:…”
Section: Model Developmentmentioning
confidence: 99%
“…These contrasting results underline that different analyses can change the perception of the type of hazard associated with hydrological processes when dissimilar metrics are used. Reconstructed rainfall erosivity in two Mediterranean fluvial basins, the Calore Basin in southern Italy (Diodato et al, 2008) and the Po Basin in northern Italy (Diodato et al, 2020c), showed similar increasing trends since the end of the LIA. If this rainfall regime continues, it could result in an increased erosive hazard affecting Mediterranean lands because erosive events occur in a more erratic way.…”
Section: Fingerprint Of Climate Changementioning
confidence: 81%
“…That exceptional event was the result of a more general regional-scale shift, which can be considered the main cause of the hydrological change that occurred during that period, also in other areas of northern Italy (Glur et al, 2013;Baldini and Bedeschi, 2018;Diodato et al, 2020c). Leonardo da Vinci himself, who knew the territory of Tuscany well, left many drawings with projects that were supposed to alleviate the effects of the increasingly dangerous floods and soil erosion (Pelucani.et al, 2017).…”
Section: Historical Rainfall Erosivity Reconstructionmentioning
confidence: 99%